If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -94y(y + -60) = y + 27 Reorder the terms: -94y(-60 + y) = y + 27 (-60 * -94y + y * -94y) = y + 27 (5640y + -94y2) = y + 27 Reorder the terms: 5640y + -94y2 = 27 + y Solving 5640y + -94y2 = 27 + y Solving for variable 'y'. Reorder the terms: -27 + 5640y + -1y + -94y2 = 27 + y + -27 + -1y Combine like terms: 5640y + -1y = 5639y -27 + 5639y + -94y2 = 27 + y + -27 + -1y Reorder the terms: -27 + 5639y + -94y2 = 27 + -27 + y + -1y Combine like terms: 27 + -27 = 0 -27 + 5639y + -94y2 = 0 + y + -1y -27 + 5639y + -94y2 = y + -1y Combine like terms: y + -1y = 0 -27 + 5639y + -94y2 = 0 Begin completing the square. Divide all terms by -94 the coefficient of the squared term: Divide each side by '-94'. 0.2872340426 + -59.9893617y + y2 = 0 Move the constant term to the right: Add '-0.2872340426' to each side of the equation. 0.2872340426 + -59.9893617y + -0.2872340426 + y2 = 0 + -0.2872340426 Reorder the terms: 0.2872340426 + -0.2872340426 + -59.9893617y + y2 = 0 + -0.2872340426 Combine like terms: 0.2872340426 + -0.2872340426 = 0.0000000000 0.0000000000 + -59.9893617y + y2 = 0 + -0.2872340426 -59.9893617y + y2 = 0 + -0.2872340426 Combine like terms: 0 + -0.2872340426 = -0.2872340426 -59.9893617y + y2 = -0.2872340426 The y term is -59.9893617y. Take half its coefficient (-29.99468085). Square it (899.6808793) and add it to both sides. Add '899.6808793' to each side of the equation. -59.9893617y + 899.6808793 + y2 = -0.2872340426 + 899.6808793 Reorder the terms: 899.6808793 + -59.9893617y + y2 = -0.2872340426 + 899.6808793 Combine like terms: -0.2872340426 + 899.6808793 = 899.3936452574 899.6808793 + -59.9893617y + y2 = 899.3936452574 Factor a perfect square on the left side: (y + -29.99468085)(y + -29.99468085) = 899.3936452574 Calculate the square root of the right side: 29.989892385 Break this problem into two subproblems by setting (y + -29.99468085) equal to 29.989892385 and -29.989892385.Subproblem 1
y + -29.99468085 = 29.989892385 Simplifying y + -29.99468085 = 29.989892385 Reorder the terms: -29.99468085 + y = 29.989892385 Solving -29.99468085 + y = 29.989892385 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '29.99468085' to each side of the equation. -29.99468085 + 29.99468085 + y = 29.989892385 + 29.99468085 Combine like terms: -29.99468085 + 29.99468085 = 0.00000000 0.00000000 + y = 29.989892385 + 29.99468085 y = 29.989892385 + 29.99468085 Combine like terms: 29.989892385 + 29.99468085 = 59.984573235 y = 59.984573235 Simplifying y = 59.984573235Subproblem 2
y + -29.99468085 = -29.989892385 Simplifying y + -29.99468085 = -29.989892385 Reorder the terms: -29.99468085 + y = -29.989892385 Solving -29.99468085 + y = -29.989892385 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '29.99468085' to each side of the equation. -29.99468085 + 29.99468085 + y = -29.989892385 + 29.99468085 Combine like terms: -29.99468085 + 29.99468085 = 0.00000000 0.00000000 + y = -29.989892385 + 29.99468085 y = -29.989892385 + 29.99468085 Combine like terms: -29.989892385 + 29.99468085 = 0.004788465 y = 0.004788465 Simplifying y = 0.004788465Solution
The solution to the problem is based on the solutions from the subproblems. y = {59.984573235, 0.004788465}
| 3(y+5)+15=7(y+6) | | 2x^2=10x-12 | | 6x-2=9x+6 | | 9y-8=3y+4 | | n+4=2n-5 | | 10x+10y=36 | | 2x-14=3x+4 | | 2w-t=4 | | 5x+1.2=3x+3.5 | | x^3-2x^2+5=0 | | 2x-10+4=4 | | x+7y=-13 | | 20=18-2x | | x^3+6x^2+9x+5=0 | | 2(-x-4)=8 | | 3(2x-1)-5=6x-8 | | x^3-6x^2+9x-5=0 | | R=6u^2v | | 2f-9=27 | | 5x+4=-61-10x | | 6x+94=11x-6 | | cos(5x)=13cos(x) | | Qd=90-5 | | x(x+8)=-20 | | 3x+32x-60=10 | | 0=-4.9x^2+107.8x+200 | | 2-3(X+4)=11 | | 4x^2+9y^2-18x+24y+9=0 | | 4y+6=-6 | | 9x+3y-8x-2y+5x+6y= | | 2x-4+8x+5+7x=18 | | 2(x+14)=8-3x |